Updated check-list of the mayflies (Insecta: Ephemeroptera) of Iraq - Khudhur, Farhad A; Sroka, Pavel (Biodiversity data journal, 2021)
Based on a recent field survey in Iraqi Kurdistan and a critical evaluation of previously published data, 37 mayfly species are listed as occurring in Iraq. We collected and identified nine species as new for the country and corrected some previously published records. For several species scarcely treated in the literature, we provide information allowing their identification in the larval stage to promote the acquisition of reliable faunistic data from Iraq in the future.
Keywords: Ephemeroptera; aquatic biodiversity; Middle East; Iraq; mayflies